Prof. Dr Dimitrije Perišić: Testimony and guidelines for spatial planning - Petrić, Jasna (Arhitektura i urbanizam, 2023)
Dedicated to Professor, Dr. Dimitrije Mita Perišić, this monograph represents a sentimental journey into the past, portraying the life and work of an extraordinary individual who was a pioneer in the field of spatial planning in our country, and serves as a guide for present and future successors who have emerged from the school founded by Professor Perišić. In this book, based on collected facts related to the professor's biography, scientific, professional, and educational work, social engagement in Yugoslavia and developing countries, public addresses, newspaper articles, awards and acknowledgments, as well as based on notes and memories of individuals about Mita Perišić, numerous details are interwoven through words and images. These details not only illustrate the value of the protagonist's scientific and professional career but also serve as a (to some extent) intimate reflection of his being. This work is not the result of one pair of hands, but is based on teamwork and the contributions of numerous participants in writing the pages presented to the readers. Stylistically consistent, with an abundance of data testifying to past times, the monograph offers a perspective and can serve as a basis for the scientific research of researchers seeking answers to questions such as: How was the first Spatial Plan of the Republic of Serbia developed? How was the study group for Spatial Planning formed at the Faculty of Mathematics and Science in Belgrade? What were the "famous" Dubrovnik meetings of spatial planners in Yugoslavia? And also: Why is Dimitrije Perišić's book on spatial planning still relevant today?
Keywords: Dimitrije Mita Perišić; spatial planning; 20th century; Yugoslavia; Serbia